PENGEMBANGAN PENDIDIKAN ASWAJA SEBAGAI STRATEGI DERADIKALISASI - Naim, Ngainun (WALISONGO, 2015)
This study discussed about the role of Aswaja lesson in the efforts of deradicalization.Radicalization had been more and more evolved since after the fallof New Order. Reformation Era opened wide varieties of expression, includedreligious expression. The development of radicalization led to widespread ofsocial unrest. Responses appeared, included using the counter-ideology. Aswajawas believed as being able to prevent the proliferation of radicalization. The datapresented in this article was derived from observation, interview and review ofthe literature related to the topic of writing. The argument developed in this paperis that the reconstruction and actualization of the values contained in Aswajamight be personally internalized firmly. An important strategy that might beapplyed to disseminate and internalize Aswaja is through education. In theschools in which applying Aswaja lesson, students had the opportunity to have amoderate religious understanding and avoid radicalization.***Penelitian ini mengulas tentang peranan pelajaran Aswaja dalam usaha deradikalisasi.Radikalisasi semakin berkembang pasca jatuhnya Orde Baru. EraReformasi membuka lebar berbagai bentuk ekspresi, termasuk ekspresi keberagamaan.Semakin berkembangnya radikalisasi memunculkan keresahan masyarakatsecara luas. Berbagai respons pun muncul, di antaranya melalui counterideologi.Aswaja diyakini dapat mencegah tumbuh suburnya radikalisasi. Datayang disajikan dalam artikel ini berasal dari observasi, wawancara dan telaahliteratur yang berkaitan dengan topik tulisan. Argumen yang dibangun dalamtulisan ini adalah rekonstruksi dan aktualisasi nilai-nilai yang terkandung didalam Aswaja dapat terinternalisasi secara kokoh dalam diri seseorang. Strategipenting yang dapat ditempuh untuk sosialisasi dan internalisasi Aswaja adalahmelalui jalur pendidikan. Di sekolah-sekolah yang mengaplikasi mata pelajaranAswaja, para siswanya memiliki peluang untuk memiliki pemahaman keagamaanyang moderat dan terhindar dari arus radikalisasi.